Sheep farming systems and management options under semi arid conditions: case of Saouaf farm in Tunisia - Ammar H.; Lahsoumi R. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The study was conducted at the farm of Saouaf belonging to the Office de l’Elevage et de Pâturage (OEP). Five sheep flocks are hosted at the farm represent two local breeds namely Barbarine or fat tailed, structured in four flocks (2 representing the black head and other 2 representing the white head types), and West thin tailed structured in one flock. The main objective of the present study was to highlight management options of the flocks, reproduction parameters and strategies of amelioration followed by OEP. All parameters of reproduction (fertility, prolificacy, fecundity, etc) were low especially for Barbarine breed. Productivity (weaned lambs/mated ewes) for both breeds was low (<100%). Artificial insemination application was traduced by an increase of prolificacy and other parameters. Results of the present study suggest that technical training of shepherds is the success key of breeding in the farms of Saouaf. Other factors such as selection of breeding rams either towards natural mating or for artificial insemination could be a useful tool to enhance productivity in both breeds.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)